Potensi Hiperglikemia Kombinasi Ekstrak Kulit Buah Semangka (Citrullus lanatus) Dan Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) - Edi Kamal, Sainal; Roosevelt, Alfreds; Patandung, Gerfan; Amiruddin, Achmad (Jurnal Farmasi Sandi Karsa, 2023)
This study aims to determine the potential hyperglycemia of the combination of Watermelon Skin Extract (Citrullus lanatus) and Red Dragon Fruit Skin Extract (Hylocereus polyrhizus). The research method used is the alloxane induction method. Rats were divided into 5 groups, namely positive control given metformin 45 mg / Kg BB, negative control given Na. CMC 1% w/v, and variations of test groups given combination extracts with concentration variations of 6% and 13.4%; 9% and 16.4%; and 12% and 19.4% then each group was induced alloxane at a dose of 24 mg / 200g BB. The results of the study on the negative control given NaCMC 1% did not show a decrease in blood sugar levels, in the positive control given metformin 45 mg / KgBB showed an average percent decrease of 94.12%, in the combination extract test group with a dose of 6% and 13.4% showed an average percent decrease of 25.04%; 9% and 16.4% % showed an average percent decrease of 24.69%; and 12% and 19.4% % showed an average percent decrease of 55.61%. Based on the results of this study, a combination extract of 12% and 19.4% can reduce blood sugar levels of white rats. This study proved that red watermelon peel extract and red dragon fruit peel extract have antihyperglycemia effects.